Projeto de arranjos de antenas microstrip patch - Andrade, Larissa Roberta [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This work presents a methodology for the design, analysis, and construction of microstrip patch antennas, that with the development of wireless communications become fundamental in the systems performance devices. The requirement for devices with compact dimensions, low cost and easy to manufacture are met by these antennas, which on the other hand has a narrow band, gain and low directivity disadvantages. In the design phase, the antenna sizing results were from the resonance frequency fr of 2.45GHz, substrate thickness (h) of 0.8mm, FR4 of dielectric constant of 4.4, and 50 input impedance. In the simulation stage from the HFSS software, parametrizations were made in order to optimize the performance of the patch antenna with one element, where the parameterizations were very sensitive to optimizations, besides a study of the impact of the choice of the tangent of losses and substrate dimensions on performance parameters such as gain and directivity. In the arrangement configuration, two strands were studied, series feeding, and in parallel. In the series arrays were designed in the simulator, two and four elements, analyzing the variation of parameters such as the distance between the elements, thickness and length of the feed line, thickness and length of the marriage structure, and the antenna format itself. The construction of the four-element series arrangement and the comparison between simulated and practical results were made proving that the project was successful. In the parallel arrangement, it was developed with power supply through a power slitting, for eight elements. The comparison of the projects with the reflection coefficient (|S11|), all presented better results than the minimum stipulated for similar projects (S11− 10dB). As for directivity, the addition of elements made the radiation pattern more directive according to the plane of addition of the elements. Finally, four series...

Este trabalho apresenta uma síntese de projeto, análise, e construção de antenas de microstrip patch, que com o desenvolvimento das comunicações sem fio, se tornam fundamentais no desempenho de sistemas. A exigência de dispositivos com dimensões menores, baixo custo e de fácil fabricação são atendidas por essas antenas, que por outro lado tem como desvantagem uma banda estreita, ganho e diretividade baixos. Na fase de projeto, os resultados de dimensionamento da antena foram a partir da frequência de ressonância fr de 2,45GHz, espessura do substrato (h) de 0,8mm, FR4 de constante dielétrica de 4,4, e impedância de entrada de 50 . Na fase de simulação a partir do software HFSS, foram feitas parametrizações a fim de otimizar o desempenho das antenas patch com um elemento, onde as parametrizações de dimensão eram muitos sensíveis a otimizações, além de um estudo do impacto da escolha da tangente de perdas e dimensões do substrato nos parâmetros de desempenho como ganho e diretividade. Na configuração de arranjo, duas vertentes foram estudadas, alimentação em série, e em paralelo. Os arranjos em série que foram projetados no simulador tinham dois e quatro elementos, e foi analisada a variação de parâmetros como na distância entre os elementos, espessura e comprimento da linha de alimentação, espessura e comprimento da estrutura de casamento, além do formato da antena em si. Foi feita a construção do arranjo em série de quatro elementos e a comparação entre resultados simulados e práticos, comprovando que o projeto foi bem sucedido. No arranjo paralelo, foi desenvolvida com alimentação através de árvore divisória de potência, para oito elementos. A comparação dos projetos quanto a coeficiente de reflexão (|S11|), todos apresentaram resultados melhor que o mínimo estipulado para projetos similares (S11 <-10dB) . Quanto a diretividade, o acréscimo de...
Microstrip patch antenna design
Keywords: Antenas (Eletrônica); Linhas de transmissão em fita; Telecomunicações; Antennas (Electronics); Strip transmission lines; Telecommunication